Profile of hyperacusis and tinnitus among traffic police exposed to noise - Abdul, Maqbool Mattathil; Rajmohan, Deekshith; S., Hemaraja Nayaka (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Traffic police are in constant risk for developing noise induced hearing loss. Studies have reported prevalent permanent threshold shift resulting to varying degrees of hearing loss. The present study was carried out with an aim of investing the prevalent Hyperacusis and Tinnitus among traffic police personnel of Mangalore, Karnataka. To profile Audiological investigations and document the prevalent Hyperacusis and Tinnitus signs and symptoms among traffic police. Methods: A total of 52 participants took part in the study in the age range of 24 to 45 years, with a mean value of 35.83±0.965 years. The study had 45 male ad 7 female participants. The Audiological evaluations were carried out. The pure tone audiometry was carried out using AC 40, two channel, diagnostic audiometer. Tympanometry was carried out using Middle ear Analyzer from Clarinet Inventis. To document the clinical signs and symptoms of Hyperacusis and Tinnitus, Modified Khalfa Hyperacusis questionnaire and Inventory of Hyperacusis Symptom (IHS) was used. Results: In our study, mean pure tone average (PTA) on right side was 13.10±0.710 dB and on left side was 13.25±0.874 dB. Pure tone average on right side ranged from 5 to 30dB and left side 4 to 30dB. It was also observed that four of the participants had mild level of Hyperacusis and one had moderate Hyperacusis and another participant with severe level Hyperacusis. Conclusions: There is a necessity to regularly monitor hearing skills and impact of noise on hearing health of traffic police personnel.